Rules of Origin and the Web of East Asian Free Trade Agreements - Manchin, Miriam (World Bank, Washington, DC, 2012)
The authors provide an overview of the preferential rules of origin in East Asia, highlighting the aspects that might possibly generate some trade-chilling effects. They review characteristics of existing preferential trade agreements with special emphasis on lessons from the European experience, and analyze some important features of the existing rules of origin in East and South-East Asian regional integration agreements. The empirical analysis of the effectiveness of preferentialism on intra-regional trade flows focuses on the ASEAN Free Trade Area (AFTA), with the aim of providing a rough estimate of the costs of requesting preferences. The results suggest that preferential tariffs favorably affect intra-regional imports only at very high margins (around 25 percentage points). This points to the likelihood of high administrative costs attached to the exploitation of preferences, particularly with regard to the compliance with AFTA's rules of origin.